Системний підхід як основа для створення автоматизованої логістичної системи - Басюк, В. С. (ХНУРЕ, 2024)
The work examines the system approach to developing an automated logistics line. The key principles of the system approach are optimality, emergencies, systematicity, hierarchy, integration, and formalization.
Keywords: автоматизовані логістичні системи; системний підхід